2004
DOI: 10.1111/j.1067-1927.2004.012504.x
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of scar tissue formation using different dermal regeneration templates in the treatment of experimental full‐thickness wounds

Abstract: The recovery of skin function is the goal of each burn surgeon. Split-skin graft treatment of full-thickness skin defects leads to scar formation, which is often vulnerable and instable. Therefore, the aim of this study was to analyze wound healing and scar tissue formation in acute full-thickness wounds treated with clinically available biopolymer dermal regeneration templates. Full-thickness wounds (3 x 3 cm) on both flanks of Gottingen mini pigs (n= 3) were treated with split-thickness skin graft alone or i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
48
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 34 publications
7
48
0
1
Order By: Relevance
“…Helbig et al [2009] reported that inflammatory cells are involved in the replacement of the necrotic zones and seem to be crucial for wound healing. However, the number of macrophages and giant cells is related to scar formation [Druecke et al, 2004]. High numbers of macrophages and giant cells are responsible for localized inflammatory reactions that could suppress further stages of wound healing and subsequently lead to scar formation [Druecke et al, 2004;Ratanavaraporn et al, 2012].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Helbig et al [2009] reported that inflammatory cells are involved in the replacement of the necrotic zones and seem to be crucial for wound healing. However, the number of macrophages and giant cells is related to scar formation [Druecke et al, 2004]. High numbers of macrophages and giant cells are responsible for localized inflammatory reactions that could suppress further stages of wound healing and subsequently lead to scar formation [Druecke et al, 2004;Ratanavaraporn et al, 2012].…”
Section: Discussionmentioning
confidence: 99%
“…However, the number of macrophages and giant cells is related to scar formation [Druecke et al, 2004]. High numbers of macrophages and giant cells are responsible for localized inflammatory reactions that could suppress further stages of wound healing and subsequently lead to scar formation [Druecke et al, 2004;Ratanavaraporn et al, 2012]. Thus, the higher number of macrophages and giant cells in wounds treated with the genipin-crosslinked PVA scaffolds without sericin could delay wound healing compared with the genipin-crosslinked sericin/ PVA scaffolds.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, they used a scale that was also used in other studies to systematically score for wound color, surface smoothness, and wound suppleness/stiffness. 169,177,180,198 Taken together, most studies provide a macroscopic but unsystematic description of wounds. To improve the comparison between studies, we recommend the use of a standard checklist: a subjective scar assessment tool could be used for this purpose, as described in Table 1.…”
Section: Constructs In Animal Modelsmentioning
confidence: 99%
“…Other studies used transparent papers to trace the wounds edges. 153,154,169 In some cases, the software used to calculate the wound area is specified. 134,137,142,146,147,150 However, differences in software is probably causing the least variation.…”
Section: Planimetry To Measure Wound Contraction And/or Re-epithelialmentioning
confidence: 99%
See 1 more Smart Citation